Reproductive and developmental toxicity of metals. - Clarkson, T W; Nordberg, Gunnar F; Sager, P R (Scandinavian Journal of Work, Environment & Health, 1985)
This paper discusses metal exposure in the male, the nonpregnant female, and the maternal-offspring unit. In the first two situations, the primary targets are the gonads. In the mother-offspring unit, consideration must be given to effects on the fertilized ovum, the growth of the embryo, and, finally, to the fetal and perinatal stages. The central nervous system may be especially vulnerable during development. The placenta also undergoes development, and either the placenta or the fetus may be the primary target. In humans, certain metals may cause abortion or other effects on the conceptus. Effects may also be produced by metal exposure both in utero and in the suckling infant. For example, methylmercury gives rise to a range of effects on the central nervous system at doses lower than those producing damage to the mature nervous system. Effects of lead and arsenic are associated mainly with postnatal exposures during infancy and early childhood, but there is reason to believe from animal experiments that some effects may occur from prenatal exposures to certain metal compounds.